Avaliação dos produtos de degradação oxidativa da Hb S em eritrócitos de doentes falcêmicos - Souza, Patricia C. [UNESP] (Elsevier, 2001)
Analysis of the products of oxidative degradation of Hb S was made by methahemoglobin measurement and a count of red blood cells with Heinz bodies. Free radicals originating from oxidation cause extensive injury to erythrocytes, decreasing their useful survival period especially in Hb S carriers. The Superoxide ion (O 2) is the most responsible for the oxidation process of Hb forming membrane-bound haemachromes which afterwards evolve to Heinz bodies, damaging the membrane and provoking erythrocytes hemolysis. The results from this work showed that the SS genotype is more susceptible to the action of the free radicals than the S/Tal genotype. The β genotype has a lower oxidative susceptibility than the SS because it has only one β s mutation. The results allowed us to conclude that: a) the simple presence of Hb S, independent of its genotype and its concentration, is sufficient to produce methaemoglobin from this Hb; b) there is not a direct relationship between methaetnoglobin concentration and the Heinz bodies count; c) the intensity of Heinz bodies in the sickled erythrocytes seems to be independent of the Hb Fetal concentration; d) The genotype SS is more susceptible to Hb oxidation with the release of products of oxidative degradation; e) methaemoglobin formation in blood of people with Hb AA and Hb AS, assessed over 24, 48, 72 and 163 hourly-periods, showed greater oxidative intensity in the Hb AS compared with Hb AA.
Evaluation of the oxidative degradation products of Hb S in sickle cell disease